Dairy buffalo production scenario in Bangladesh: a review - Habib, Md Rezwanul; Haque, Md Najmul; Rahman, Ashikur; Aftabuzzaman, Md; Ali, Md Mahabbat; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2017)
The objective of this review is to draw the present scenario of dairy buffalo production in Bangladesh and their contributions to the national economy. Buffaloes in Bangladesh are mostly indigenous type encompasses with swamp and river and are distributed throughout the country. However, the population is higher in coastal part, Meghna-Ganga and Jamuna-Brahamaputra flood plain, considered to be the buffalo pockets. The total buffalo population is 1.471 million which are mostly managed in household subsistence farming as well as bathan in coastal region. Buffaloes are normally used as a draught animal and in lower extent partially for milk and meat production. Most of the farmers are rural small holders; traditionally practiced crop-livestock integration upon which the management practices of buffalo usually depends. Buffaloes are raised in homestead and approximately 5-7 hours were grazes per day in household farming. Small amount of concentrate is usually offered to buffalo during dry season only by the economically viable farmers. On the other hand, in bathan, farmers are fully depended on grazing at public fallow land. Lower milk production efficiency, poor reproductive performance followed by under nutrition and low growth rate in buffaloes resulted insignificant contribution to the national economy of Bangladesh. Balanced nutrition and better management practices can improve buffalo productivity. In order to do so, a number of issues are required to be addressed such as establishment of nutrient requirements for dairy, development of buffalo calf feeding systems, artificial insemination technique, nutritional management of metabolic and reproductive anomalies, and understanding and exploitation of the buffalo gut ecosystem. Productivity of buffaloes can be mainly depended on genetic improvement, good nutrition, good management and also climatic conditions of an area. Extensive coordinated research and extension efforts are required for increasing dairy buffalo production in this country. Asian J. Med. Biol. Res. September 2017, 3(3): 305-316